2021
DOI: 10.1021/acsomega.1c02938
|View full text |Cite
|
Sign up to set email alerts
|

Blind Spot: A Braille Patterned Novel Multiplex Lateral Flow Immunoassay Sensor Array for the Detection of Biothreat Agents

Abstract: Lateral flow immunoassays (LFIs) are simple, point-of-care diagnostic devices used for detecting biological agents or other analytes of interest in a sample. LFIs are predominantly singleplex assays, interrogating one target analyte at a time. There is a need for multiplex LFI devices, e.g., a syndromic panel to differentiate pathogens causing diseases exhibiting similar symptoms. Multiplex LFI devices would be especially valuable in instances where sample quantity is limiting and reducing assay time and costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…The manual method of preparing the T-line makes it challenging to ensure repeatability and uniformity in cutting from one device to another. To address this issue and facilitate upscale production, we propose the use of an automated system, such as a NanoDrop instrument (AD1520 Aspirate AD1520 Aspirate Dispense System), 36 for creating the T-line. This machine can precisely control the volume and position of each drop.…”
Section: Resultsmentioning
confidence: 99%
“…The manual method of preparing the T-line makes it challenging to ensure repeatability and uniformity in cutting from one device to another. To address this issue and facilitate upscale production, we propose the use of an automated system, such as a NanoDrop instrument (AD1520 Aspirate AD1520 Aspirate Dispense System), 36 for creating the T-line. This machine can precisely control the volume and position of each drop.…”
Section: Resultsmentioning
confidence: 99%
“…Large-scale manufacturing of xLFTs requires the printing of multiple test spots in a single disposable strip, and thus, multiple dispensing nozzles with different quality-control measures, potentially increasing production costs. Furthermore, additional test lines complicate result interpretation, although this can be mitigated through use of digital interpretation or test spot array patterns that are recognizable to users 166,167 . The development and commercialization of xLFTs are further limited by the need to validate multiple biomarkers with clinical importance, low market demand and a complicated regulatory approval pathway.…”
Section: Multiplexingmentioning
confidence: 99%
“…Kazushi Misawa et al demonstrated the semiquantitative, visual result readout in the form of “text”. This intuitive signal method offered potential for an alternative and suitable POC testing application . Traditional LFAs use colloidal AuNPs as a signal for qualitative diagnostic detection.…”
Section: Recent Advances In Lfas For Biomarker Detectionmentioning
confidence: 99%